2016
DOI: 10.3354/aei00186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on mortality of Pacific oysters Crassostrea gigas associated with microvariant ostreid herpesvirus 1 (OsHV-1 µVar)

Abstract: The ostreid herpesvirus 1 microvariant (OsHV-1 µVar) causes mass mortality of Pacific oysters Crassostrea gigas. Water temperature can directly influence the incidence of disease or correlate with seasonal changes in the environment and oyster physiology that modify the susceptibility of the oysters to disease. The effect of water temperature was evaluated in controlled laboratory conditions by intramuscular injection of OsHV-1 µVar after acclimation of 8 mo old spat and 17 mo old adult oysters at 4 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In temperate zones, on the other hand, high temperatures, particularly in summer events, can adversely affect growth and survival due to stress and susceptibility to diseases (Kantzow, Hick, Becker, & Whittington, ). Similarly, in subtropical areas (north coast of the Pacific coast of Mexico), it has been observed that increasing temperature in summer inhibits growth of shell as well as soft tissue in C. gigas producing physiological stress (Castillo‐Duran, Chavez‐Villalba, Arreola‐Lizarraga, & Barraza‐Guardado, ; Chávez‐Villalba, Arreola‐Lizárraga, Burrola‐Sánchez, & Hoyos‐Chairez, ).…”
Section: Discussionmentioning
confidence: 99%
“…In temperate zones, on the other hand, high temperatures, particularly in summer events, can adversely affect growth and survival due to stress and susceptibility to diseases (Kantzow, Hick, Becker, & Whittington, ). Similarly, in subtropical areas (north coast of the Pacific coast of Mexico), it has been observed that increasing temperature in summer inhibits growth of shell as well as soft tissue in C. gigas producing physiological stress (Castillo‐Duran, Chavez‐Villalba, Arreola‐Lizarraga, & Barraza‐Guardado, ; Chávez‐Villalba, Arreola‐Lizárraga, Burrola‐Sánchez, & Hoyos‐Chairez, ).…”
Section: Discussionmentioning
confidence: 99%
“…De Kantzow et al . () also showed the direct effect of water temperature on infection and disease by removing the field variables using laboratory challenge with OsHV‐1 μVar and they indicated that infection did not take place below a threshold temperature of 14–18°C.…”
Section: Environment Factorsmentioning
confidence: 99%
“…), which was supported by De Kantzow et al . () who showed in laboratory experiments that 8‐month‐old spat were 2.7 times more likely to die after challenge with OsHV‐1 μVar than 17‐month‐old adults.…”
Section: Animal Host Factorsmentioning
confidence: 99%
“…De Kantzow et al . () exposed spat and adult oysters to OsHV‐1 μVar at different temperatures (14, 18, 22 and 26°C) and found direct influence of water temperatures on oyster mortalities caused by OsHV‐1 μVar exposure. Indeed, no mortality was recorded at 14°C and mortalities at 18, 22 and 26°C were 23, 77 and 84%, respectively.…”
Section: Interactions Between Pathogen Infection and Abiotic Factorsmentioning
confidence: 99%